Response to "The Seven‐Membered Ring in Bis‐Azuleno‐Naphthalene is Non‐Aromatic". Issue 4 (23rd January 2019) - Uehara, Keiji; Mei, Peifeng; Murayama, Tomohisa; Tani, Fumito; Hayashi, Hironobu; Suzuki, Mitsuharu; Aratani, Naoki; Yamada, Hiroko
Abstract : The magnetic properties of the compound (Az2 ) we have reported earlier were investigated by using NICSπ, zz and NICS‐XY scans by Stanger. His conclusions are that the seven‐membered ring in Az2 is not antiaromatic but non‐aromatic, thus the small paratropic values are the result of three diatropic moieties that surround this ring. Based on the same data, we discuss the ring current at the new seven‐membered ring carefully. Abstract : Stanger's conclusions are that the seven‐membered ring in Az2 is not antiaromatic but non‐aromatic, thus the small paratropic values are the result of three diatropic moieties that surround this ring. Based on the same data, we discuss the ring current at the new seven‐membered ring.